Behaviour of steel-BFRP bars reinforced ECC composite girders with corrugated webs under negative moment. (April 2023) - Wu, Fangwen; Fan, Zhou; He, Lanqing; Li, Zirun; Liu, Shuo; Yang, Fei
Abstract: To improve the durability of steel–concrete composite girders with corrugated webs subjected to negative moments, basalt fibre reinforced polymer (BFRP) bars and engineered cementitious composite (ECC) were used to substitute for steel bars and normal concrete (NC), respectively. Experimental and numerical investigations were conducted to explore the mechanical properties of steel-BFRP bars reinforced ECC composite girders with corrugated webs. First, four composite girders considering concrete and reinforcement types were tested subjected to negative moments. The failure modes, flexural stiffness, bearing capacity, vertical displacement, strain, and crack propagation law were analysed and compared. Steel-ECC girders have higher flexural stiffness, bearing capacity, and better crack control capability than steel-NC girders. After that, the numerical models considering material nonlinearity were established and validated. Moreover, numerical investigations indicated that the steel girder considerably affects the flexural stiffness and bearing capacity. Increasing the thickness of the corrugated web is the most effective way to improve the structural ultimate bearing performance. Finally, the calculated negative bending capacity according to the codes is compared with the experimental one, and suggestions for code improvement are proposed to promote the application of new materials in structures.